2006
DOI: 10.1002/jcu.20234
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of focal liver lesions using contrast-enhanced sonography with a low mechanical index mode and a sulfur hexafluoride-filled microbubble contrast agent

Abstract: Low-mechanical index CEUS permits real-time, complete assessment of vascularity in FLLs, which in turn facilitates their characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 27 publications
9
99
2
2
Order By: Relevance
“…This progressive neo-angiogenesis provides the clue for clinical diagnosis with imaging techniques [28] . HCC typically exhibits arterial hyper-perfusion compared with the surrounding liver tissue at the time when in the surrounding liver parenchyma no contrast effect is as yet discernible ( Figure 1) [29] . Uneven arterial hyper-enhancement of HCC may be noted, because the tumors may have septa, different cell differentiation and arterio-venous shunting patterns among the neo-formed vessels [30] .…”
Section: Detection Of Malignant Flls In Cirrhotic Liver With Ceusmentioning
confidence: 99%
See 1 more Smart Citation
“…This progressive neo-angiogenesis provides the clue for clinical diagnosis with imaging techniques [28] . HCC typically exhibits arterial hyper-perfusion compared with the surrounding liver tissue at the time when in the surrounding liver parenchyma no contrast effect is as yet discernible ( Figure 1) [29] . Uneven arterial hyper-enhancement of HCC may be noted, because the tumors may have septa, different cell differentiation and arterio-venous shunting patterns among the neo-formed vessels [30] .…”
Section: Detection Of Malignant Flls In Cirrhotic Liver With Ceusmentioning
confidence: 99%
“…Uneven arterial hyper-enhancement of HCC may be noted, because the tumors may have septa, different cell differentiation and arterio-venous shunting patterns among the neo-formed vessels [30] . In the portal and late phase, HCC are usually hypo-enhanced, as the UCA will wash out from HCC to the liver parenchyma rapidly, and the tumor may appear hypo-enhanced with respect to the surrounding liver in the late phase [24,25,29] . As some regenerative nodules may also exhibit additional arterial enrichment, analysis of the portal venous phase makes the differentiation of these iso-enhanced nodules from hypo-enhanced HCC possible.…”
Section: Detection Of Malignant Flls In Cirrhotic Liver With Ceusmentioning
confidence: 99%
“…8,9 However, very few studies have described the imaging appearance of ICC by CEUS, and in most cases they included large tumors in noncirrhosis patients. [10][11][12][13][14][15][16] For that reason there is no accurate information regarding the appearance of ICC after CEUS in cirrhosis patients, and particularly in small nodules detected during screening. In this setting the diagnostic difficulties may be higher and, as previously mentioned, it is key to distinguish between HCC and ICC to permit a proper treatment indication.…”
mentioning
confidence: 99%
“…Furthermore, it was demonstrated that the diagnostic accuracy of SonoVue ® enhanced ultrasound was better in comparison to C CT and CMR [14] . Hohmann et al [15] using MBs agents in C-US with a long-lasting late phase, showed no significant difference in lesion detection compared with CMR imaging.…”
Section: C-usmentioning
confidence: 99%